Типові психологічні профілі працівників поліції (за результатами застосування опитувальника Міні-Мульт) - Барко, В. І.; Barko, V. I.; Барко, В. В.; Barko, V. V.; Євдокімова, О. О.; Yevdokimova, O. O.; Olena Yevdokimova (Вісник Національного університету оборони України. - 2024. - № 2 (78). - С. 7-17, 2024)
Стаття присвячена проблематиці вивчення й аналізу індивідуально-особистісних психологічних профілів працівників поліції, отриманих на основі багаторічного дослідження із застосуванням адаптованої авторами українськомовної психодіагностичної методики «Міні-Мульт», розробленої І. Кінканнон. Представлені в статті результати містять описання різних типів індивідуальноособистісних профілів, які характеризуються як сприятливі, менш сприятливі і несприятливі для службової діяльності в системі Національної поліції України залежно від типологічних особливостей, специфіки провідних тенденцій, властивостей мислення, комунікації, типу реакції на стрес тощо.

The purpose of this article is to highlight and analyze the main types of individual and personal profiles of police officers in order to provide psychologists of psychological support units with the opportunity to scientifically substantiate and quickly draw conclusions about the degree of psychological suitability of a candidate for service or for a position, as well as to carry out psychological counseling of working police officers in the direction of improvement and development of their professionally important individual characteristics. It is shown that thirteen types of psychological profiles are typical for police officers interviewed, including approximately half of the employees have a sthenic type of response, a third have a mixed type, and a tenth have a hyposthenic type. Recommendations for psychologists are also presented regarding the comprehensive consideration of various combinations of scales when formulating a conclusion of professional suitability and establishing possible variants of maladjustment - hysterical, neurasthenic, depressive, hypochondriac and other types of behavior. It is also shown that based on the results of this questionnaire, psychologists can make well-founded conclusions about the degree of a person's suitability for professional activity.

Статья посвящена проблематике изучения и анализа индивидуально-личностных психологических профилей работников полиции, полученных на основе многолетнего исследования с применением адаптированной авторами украиноязычной психодиагностической методики «Мини-Мульт», разработанной И. Кинканнон. Представленные в статье результаты содержат описание различных типов индивидуально-личных профилей, которые характеризуются как благоприятные, менее благоприятные и неблагоприятные для служебной деятельности в системе Национальной полиции Украины в зависимости от типологических особенностей, специфики ведущих тенденций, свойств мышления, коммуникации, типа реакции на стресс и т.д.
Keywords: опитувальник Міні-Мульт; психологічна придатність; стрес; деадаптація; індивідуально-особистісний психологічний профіль; працівник поліції; психологічна придатність; стрес; деадаптація; questionnaire “Mini-Mult”; individual-personal psychological profile; police officer; psychological fitness; stress; maladaptation; опросник Мини-Мульт; индивидуально-личностный психологический профиль; работник полиции; психологическая пригодность; стресс; деадаптация